Teaching psychotherapy in the medical profession in Peru - Valle, Rubén (2020)
Psychotherapy seeks to modify abnormal behavior and promote normal behaviors through psychological and attitudinal means, as well as corrective experiences. Its utility is reflected in clinical practice guidelines that place it within the first lines of treatment for mental disorders. In Peru, physicians are trained in psychotherapy in the medical school and the psychiatry residency program. However, some problems are reported in his teaching. Only some medical schools offer psychotherapy classes; and among whose do, they invest few hours of teaching. In the psychiatry residency program, some residents report not holding theoretical classes, or practices that allow them to apply support psychotherapy. Also, graduate psychotherapy programs, apart from the psychiatry residency program, are few. The manuscript analyzes psychotherapy training in the medical profession, and proposes a teaching structure according to the stages of study.